2020
DOI: 10.1044/2020_aja-20-00022
|View full text |Cite
|
Sign up to set email alerts
|

Interrater Reliability for a Two-Interval, Observer-Based Procedure for Measuring Hearing in Young Children

Abstract: Purpose To overcome methodology limitations for studying auditory development in young children, we have recently developed an observer-based procedure that uses a conditioned, play-based, motor response (see Bonino & Leibold, 2017). The purpose of this article was to examine interrater reliability for the method. Method Video recordings of test sessions of 2- to 4-year-old children ( n = 17) were examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…Kappa statistics for individual test sessions ranged from 0.62 to 0.94. These kappa statistics are consistent with previous estimates of inter-rater reliability for the PlayO2I method with a tone detection in quiet task (Bonino et al 2020). Thus, results from this subset of participants suggest excellent inter-rater reliability for the present study.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Kappa statistics for individual test sessions ranged from 0.62 to 0.94. These kappa statistics are consistent with previous estimates of inter-rater reliability for the PlayO2I method with a tone detection in quiet task (Bonino et al 2020). Thus, results from this subset of participants suggest excellent inter-rater reliability for the present study.…”
Section: Resultssupporting
confidence: 90%
“…Data quality metrics (e.g., probe hit rate, observer confidence) were similar for 2- to 4-year-old children and adults. Moreover, estimates of inter-rater reliability in the present study agreed with those reported for a tone detection in quiet task (Bonino et al 2020). Thus, these results suggest similar success for measuring 2- to 4-year-old children’s hearing abilities with the PlayO2I method for complex stimuli as has been previously reported for simple stimuli.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations